Essentials of ecology - Miller, G. Tyler; Spoolman, Scott (National Geographic Learning, Cengage Learning, 2015)
Designed to equip students with the inspiration and knowledge they need to make a difference solving environmental issues, this book covers scientific principles and concepts, ecosystems, evolution, biodiversity, population ecology, and more.